Principles and Perspectives in Cosmochemistry Lecture Notes of the Kodai School on 'Synthesis of Elements in Stars' held at Kodaikanal Observatory, India, April 29 - May 13, 2008 - Goswami, Aruna; Reddy, B. Eswar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
A fundamental question in contemporary astrophysics is the origin of the elements. Cosmochemistry seeks to answer when, how and where the chemical elements arose. Quantitative answers to these fundamental questions require a multi-disciplinary approach involving stellar evolution, explosive nucleosynthesis and nuclear reactions in different astrophysical environments. There remain, however, many outstanding problems and cosmochemistry remains a fertile area of research. This book is among the first in recent times to put together the essentials of cosmochemistry, combining contributions from leading astrophysicists in the field. The chapters have been organized to provide a clear description of the fundamentals, an introduction to modern techniques such as computational modelling, and glimpses of outstanding issues.
Stellar Structure, Nucleosynthesis and Evolution of Low and Intermediate-mass Stars -- Stellar Structure and Evolution: An Introduction -- Nucleosynthesis of Low and Intermediate-mass Stars -- Spectral Classification: Old and Contemporary -- Massive Stars, Core Collapse, Explosive Nucleosynthesis -- Weak Interaction Rates for Stellar Evolution, Supernovae and r-Process Nucleosynthesis -- Massive stars as thermonuclear reactors and their explosions following core collapse -- The Evolution of Massive Stars and the Concomitant Non-explosive and Explosive Nucleosynthesis -- Cosmochemistry and Solar System Abundances -- Cosmochemistry -- Solar System Abundances of the Elements -- Cosmochemistry: A Perspective.
Keywords: Astrophysics; Nuclear fusion; Astrophysics and Astroparticles; Nuclear Fusion